INDONESIAN BAY LEAVES AS ANTIDIABETIC FOR TYPE 2 DIABETES MELLITUS - -, Taufiqurrohman (Majority, 2015)
Abstract The incidence of infectious diseases to non-communicable diseases are increasing globally. Diabetes mellitus( DM ) has ranking the top ten causes of death and The most frequently ill. The disease is thought to have something to do with the way of life that no changes are less healthy diet . This is a factor common cause of type 2 diabetes mellitus incidence and prevalence of diabetes continues to rise each year, more than 392 million people worldwide suffer from diabetes in 2013 is expected to increase worldwide in 2035 with 592 million people. Indonesia ranks fourth with 8,4 million people with diabetes. Indonesia ranks 4th in the world for patients DM. Medicinal plants reported to be safer than synthetic drugs. In addition, the price is relatively cheaper and has minimal side effects. The use of traditional medicinal plants should need to be considered in the treatment of diabetes. The use of natural ingredients that can be used as an alternative treatment for type 2 diabetes mellitus is an Indonesian bay leaf (Syzygium polyanthum (wight) Walp) containing antidiabetic. Indonesian bay leaves have active compounds such as eugenol, tannins and flavonoids. Leaves has potential as an antidiabetic drug for patients with type 2 diabetes mellitus. Keyword : antidiabetic,bay leaf, Syzygium polyanthum,type 2 diabetes mellitus Abstrak Kejadian terhadap penyakit menular ke penyakit tidak menular yang secara global terus meningkat, secara nasional telah menduduki sepuluh penyakit terbanyak penyebab kematian dan kasus terbanyak di antaranya adalah penyakit diabetes melitus (DM). Penyakit ini diduga ada hubungannya ada dengan cara hidup yang berubah yaitu pola makan yang kurang sehat. Hal ini merupakan faktor penyebab tersering diabetes melitus tipe 2.Insidens dan prevalensi DM setiap tahunnya terus meningkat, lebih dari 392 juta orang di dunia menderita DM pada tahun 2013 diperkirakan akan meningkat diseluruh dunia pada tahun 2035 menjadi 592 juta penderita. Indonesia menempati urutan ke–4 di dunia untuk jumlah penderita DM. Tanamanobat dilaporkan lebih aman dibandingkan dengan obat sintetik. Selain itu, harganya relatif lebih murah dan memiliki efek samping yang minimal. Penggunaan tanaman obat tradisional sebaiknya perlu dipikirkan dalam penyembuhan diabetes. Penggunaan bahan alami yang dapat digunakan sebagai alternatif pengobatan terhadap diabetes melitus tipe 2 adalah daun salam Syzygium polyanthum (wight) Walp yang mengandung antidiabetik. Daun salamyang memiliki senyawa aktif sepertieugenol, tannin dan flavonoid. Daun salam memiliki potensi sebagai antidiabetes untuk pasien diabetes melitus tipe 2. Kata Kunci :antidiabetes, diabetes melitus tipe 2, saun salam, syzygium polyanthum